The Reversal of Inhibitors in Congenital Hemophilia. Issue 2 (25th January 2013) - DeFrates, Sean R.; McDonagh, Kevin T.; Adams, Val R.
<x xml:space="preserve">Abstract</x> Hemophilias A and B are heritable bleeding disorders characterized by deficient baseline levels of factor VIII (fVIII) and factor IX (fIX), respectively. Standard treatment for acute bleeding events and for prophylaxis in patients with severe disease consists of recombinant fVIII and fIX infusions. The development of alloantibodies, or inhibitors, is a serious complication of congenital hemophilia that may impair the effectiveness of fVIII and fIX, leading to increased morbidity and cost of therapy. When inhibitors are present, bypassing agents such as recombinant activated factor VII and factor eight inhibitor bypass agent are available for treatment of bleeding events. Although usually effective, they are costly treatments. Immune‐modulatory therapy may reverse inhibitors, allowing fVIII and fIX to be used again. Immune tolerance induction is the chief treatment option to decrease inhibitor levels, but about 20–30% of patients fail this treatment. Alternatively, multiple immune‐modulating agents have been tried with limited success. Rituximab, an anti‐CD20 monoclonal antibody, is one therapy that has been successful in reducing inhibitor titers in multiple case reports. Although current evidence is limited and questions regarding its use and place in therapy still exist, this agent shows promise for the future.